Pengembangan Media Pembelajaran Menggunakan Model CAI Sebagai Upaya Memperbaiki Kualitas Pembelajaran Pada Mata Kuliah Fisika Optik - Ismayati, Euis (Faculty of Technological and Vocational Education-Universitas Pendidikan Indonesia, 2011)
This research aims to develop instructional media products with the computer based instructionsÂ in Physics Optical subject matter for S1 Electrical Engineering students, know the difference learning outcomes between students who use instructional media and students who do not use instructional media, and to study the response of students to instructional media with computer based instructions. The research was conducted in two stages: 1) preliminary research stage,Â Â research and development which is carried out to develop an interactive instructional media products for Optical Physics. 2) Further research using action research class method, the steps using the model of Lewin. The research consisted of four cycles, in which researcher as a teacher as well as research instruments. The results showed that the instructional media products that are developed enough to attract students which is indicated from the increase of learning outcomes and positive response from students.